Total quality management in pre-press: a study of book printers in Ibadan, Nigeria (2016)
Quality control (QC) in a book printing firm is prerequisite for excellence in production therefore it should be incorporated into the day-to-day activities of printing companies. It was observed that books produced by printers in Ibadan are generally of average quality. This study therefore investigated how printers can incorporate Total Quality Management (TQM) into printing processes to ensure high quality production. Survey method was adopted, structured questionnaire was the instrument employed while three research questions were formulated. Book printers constituted the population of the study and 110 were randomly selected as sample. The 110 copies of the questionnaire administered were duly returned. The data collected was analysed using percentages and statistical mean. Findings revealed that most of the printing firms neither have QC department, personnel, nor have heard of TQM. The study recommended that the installation of TQM in pre-press operations in Ibadan is a recipe for quality book production.